A DESCRIPTIVE STUDY OF STUDENTS' PREFERENCES IN LEARNING ENGLISH VOCABULARY THROUGH DIGITAL APPLICATIONS - Muhammad Fadhil Al Fath (Conscientia - Journal on Language, Literature, and Culture, 2026)
The rapid growth of technology has significantly influenced language learning, particularly in the acquisition of English vocabulary through digital tools. While EFL learners often struggle with vocabulary due to the sheer volume of core words and the complexity of word mastery, the continuous evolution of modern technology provides innovative ways to tackle these difficulties. Consequently, students could enhance their word knowledge through various digital platforms, ranging from mobile applications and web-based communication tools to electronic glossaries and interactive gaming. This study aimed to describe the preferences of students at STBA LIA Yogyakarta in learning English vocabulary using digital applications, identifying the specific tools and features that provide for their needs. A descriptive quantitative methodology was employed, involving 20 students selected through purposive sampling who have experience using digital vocabulary tools. Data were collected using a systematic questionnaire and analyzed through descriptive statistical techniques, focusing on frequency and percentage distributions. The findings reveal a significant preference among students for specific digital applications, leading to the rejection of the null hypothesis. Duolingo emerged as the most dominant application, used by 55% of respondents, followed by Quizizz (25%) and Kahoot (15%). In terms of usage patterns, 65% of students utilize these applications 1-2 times per week, indicating a moderate but consistent integration of digital tools into their study routines. The study concluded that the interactive and gamified features of applications like Duolingo are highly valued by learners. These results suggested that educators and developers should focus on user-friendly, engaging designs to optimize vocabulary learning strategies and cater to diverse student habits.